2022
DOI: 10.3390/horticulturae8050394
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Callus and Cell Suspension Cultures of Lycium schweinfurthii for Improved Production of Phenolics, Flavonoids, and Antioxidant Activity

Abstract: Lycium schweinfurthii is a traditional medicinal plant grown in the Mediterranean region. As it is used in folk medicine to treat stomach ulcers, it took more attention as a source of valuable secondary metabolites. The in vitro cultures of L. schweinfurthii could be a great tool to produce secondary metabolites at low costs. The presented study aimed to introduce and optimize a protocol for inducing callus and cell suspension cultures as well as estimating phenolic, flavonoid compounds, and antioxidant activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 80 publications
0
9
0
Order By: Relevance
“…The plant material of L. schweinfurthii callus cultures was obtained from leaf explants according to the method of Mamdouh and Smetanska (2022). The obtained callus was sub-cultured on MS (Murashige and Skoog) medium (Duchefa, Haarlem, The Netherlands) supplemented with 2 mg L − 1 NAA (Mallinckrodt, Hazelwood, MO), 30 g L − 1 sucrose, and 8 g L − 1 solidifying agar (Duchefa).…”
Section: Plant Materialsmentioning
confidence: 99%
“…The plant material of L. schweinfurthii callus cultures was obtained from leaf explants according to the method of Mamdouh and Smetanska (2022). The obtained callus was sub-cultured on MS (Murashige and Skoog) medium (Duchefa, Haarlem, The Netherlands) supplemented with 2 mg L − 1 NAA (Mallinckrodt, Hazelwood, MO), 30 g L − 1 sucrose, and 8 g L − 1 solidifying agar (Duchefa).…”
Section: Plant Materialsmentioning
confidence: 99%
“…L. schweinfurthii is a member of the Solanaceae family that is naturally distributed along the African coastal area, Sicily, Cyprus, and Crete (Boulos, 2002). Its leaves and fruits are used in traditional medicine due to its contents of alkaloids, glycosides, sterols, saponins, resins, phenolics, and flavonoids (Mamdouh and Smetanska, 2022). Although the limited distribution areas, Shaltout et al (2018) reported that this species is distributed in many habitats (coastal sand dunes, flat sand sheets, roadsides, island sand dunes, and canal banks) along the Mediterranean coast in Egypt.…”
Section: Study Speciesmentioning
confidence: 99%
“…According to the authors [86], such results can be useful in the large-scale production of phenols with antioxidant activity. Another biotechnological way to produce secondary metabolites is through in vitro micropropagated plants, and this approach was also made by the same group [88], who developed a protocol for in vitro micropropagation of L. schweinfurthii with genetic stability, assessed through a random amplified polymorphic DNA (RAPD), inter-simple sequence repeats (ISSR), and one biochemical technique, sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE), able to scavenge free radicals and produce phenols. The leaves of the micropropagated plants produced phenols, measured as total phenols and total flavonoids, and one phenolic acid (ferulic acid) was identified by high performance thin-layer chromatography (HPTLC).…”
Section: Biotechnological Production Of Secondary Metabolitesmentioning
confidence: 99%
“…The capacity for scavenging the DPPH and ABTS free radicals were IC 50 = 0.43 and 1.99 mg/mL, respectively. As aforementioned, the authors [88] considered that micropropagated plants of L. schweinfurthii can be another way to obtain plant material for in vitro secondary metabolite production. Nevertheless, nothing is reported about the production of clones with the best capacity for accumulating the secondary metabolites with antioxidant activity.…”
Section: Biotechnological Production Of Secondary Metabolitesmentioning
confidence: 99%